Audited Financial Statements, Financial Literacy, Perceived Audit Costs, And Access To Financing Among Culinary - Giovanny Kristianto; Dianningsih (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2026)
This study offers originality by examining access to financing among culinary MSMEs through the combined lens of audited financial statements, financial literacy, and perceived audit costs, a relationship that remains underexplored in the local context of Banyumas Regency. The study aims to analyze whether these three factors influence the ease of access to external financing for culinary MSMEs. A quantitative explanatory approach with a cross-sectional survey design was employed. Data were collected from 135 owners/managers of culinary MSMEs affiliated with ASPIKMAS Patikraja, Banyumas Regency, using a structured questionnaire with a five-point Likert scale. The data were analyzed using PLS-SEM with bootstrapping of 5,000 resamples. The empirical results show that the model has very weak explanatory power (R² = 0.011), and none of the proposed predictors significantly affect financing access: audited financial statements (β = −0.097; p = 0.256), financial literacy (β = −0.002; p = 0.977), and perceived audit costs (β = −0.039; p = 0.670). These findings imply that financing access among culinary MSMEs is likely shaped more by contextual lending factors, such as collateral, cash-flow stability, business legality, and relationship lending, than by audit-related attributes alone